Hubungan antara Dukungan Sosial Keluarga dengan Prokrastinasi Akademik pada Mahasiswa Perantau (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2020)
This research aims to determine how far relationship between family social support with academic procrastination in overseas students. Academic procrastination is an activity or habit that is put off a job, by doing activities that are not important. This research consists of independent variable is family social support and dependent variable is academic procrastination. The hypothesis in this research is that there is a negative relationship between family social support and academic procrastination of overseas students. This means that the better or more positive the perception of family social support, the lower the procrastination behavior. Conversely, the lower or the more negative the perception of family social support, the higher the academic procrastination of overseas students. Participants in this research were 100 participants who were focused on the class of 2016 overseas students at the University of 17 Agustus 1945 Surabaya. Data analysis technique used a Product Moment correlation test using SPSS software version 20 for windows, the results of which obtained a correlation coefficient of rxy = -0,368 with a significance value of p = 0,000 < from 0,05, so the results of this research had a negative correlation and very significant.Keywords: Academic Procrastination, Family Social Support, Overseas Students.